Frequency and Patterns of Eye Diseases in Retina Clinic of a Tertiary Care Hospital in Karachi - Umair Qidwai, Umer Qazi, Aimal Khan, Qamar Riaz, Fayaz Soomro (Pakistan Journal of Ophthalmology, 2011)
Purpose: To evaluate the Frequency and Pattern of Eye Diseases in Retina Clinic of a Tertiary Care Hospital in Karachi Material and Methods: A total number of 27,000 new patients were seen at the Al Ibrahim Eye Hospital (AIEH), retina clinic between July 2009 and June 2010, their data was obtained from the ophthalmic outpatient attendance register. Their records were analyzed for data according to age, sex and clinical diagnoses made after detailed fundus evaluation with binocular indirect ophthalmoscope and slit lamp using 20 D and 90 D lenses respectively. Data was entered and analyzed for simple frequency using SPSS version 14.0. Tests for significant inter group differences were performed using the chi square test with a p<0.001 considered statistically significant. Results: Out of 27,000, 3615 patients were registered in retina clinic. Diabetic related retinal conditions were the most common cause (39.8%) for registration in the retina clinic. 648 (45% of total DR) patients had clinically significant macular edema (CSME) and 102 (7%) eyes had advanced diabetic eye disease (ADED). Conclusion: There is a tremendous impact of increasing retinal blindness secondary to retinal diseases especially diabetic retinopathy in Pakistan. The impression based on hospital practice is that the problem is on the rise. This entails the necessity for accessible comprehensive eye care services, establishment of human resources, screening and awareness of the disease and affordable eye health policy.